2009
DOI: 10.1116/1.3167363
|View full text |Cite
|
Sign up to set email alerts
|

Effects of nitrogen doping of ZnO during or after deposition

Abstract: Effects of (P, N) dual acceptor doping on band gap and p-type conduction behavior of ZnO filmsEffects of nitrogen doping of ZnO ͑ZnO:N͒ during deposition and after postdeposition annealing have been studied by optical techniques, electronic properties, and the application to metal-semiconductor-metal photodetectors ͑MSM-PDs͒. Films of ZnO, nitrogen doped during rf sputtering, show larger grain size, narrower full width at half maximum, band gap emission shift in photoluminescence, and higher conductivity. Post… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 23 publications
(13 reference statements)
0
6
0
Order By: Relevance
“…One possible reason of this may be that the energy of implanted ions is transferred to the unimplanted ZnO layer. Yen et al [14] reported that nitrogen doping provided better crystal quality of ZnO films. However, this is different from the reported results of Wang et al [15].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One possible reason of this may be that the energy of implanted ions is transferred to the unimplanted ZnO layer. Yen et al [14] reported that nitrogen doping provided better crystal quality of ZnO films. However, this is different from the reported results of Wang et al [15].…”
Section: Resultsmentioning
confidence: 99%
“…Besides the magnetism, the photoluminescence (PL) and electrical conductivity of nitrogen-doped ZnO were also intensively investigated [14][15][16][17][18][19][20][21]. Recently reported results [21] indicate that nitrogen dopant cannot induce p-type conductivity in ZnO as it is a deep acceptor in ZnO.…”
Section: Introductionmentioning
confidence: 99%
“…However, the main drawback of the MSM-PD is high dark current due to the Schottky barrier junction. In this paper, we have reached lower dark current of MSM-PDs by adopting various post-processing steps to modify the properties of ZnO thin films [2,3] and in addition, have investigated the current transport mechanisms of MSM-PDs.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that adulteration is one of the effective ways to modulate the performance of ZnO nanomaterials, furthermore, the intrinsic ZnO nanomaterials are favorable for energy and photoelectric devices [13][14][15][16]. There are many studies on the properties of Zno nanowires based on first-principles calculations, including native point defects, magnetic and optical properties [17][18][19].…”
Section: Introductionmentioning
confidence: 99%